THE COVID-19 INFORMATION IMPACT ON MOVEMENT AND VOLATILITY OF ASEAN-5 CURRENCY - Muhammad Rifki Adiyat; Dwi Nastiti Danarsari (Fakultas Ekonomi dan Bisnis Universitas Padjadjaran, 2022)
The rapid and massive spread of COVID-19 has a major impact on a country's economy, including ASEAN countries. This research aims to examine the impact of the COVID-19 outbreak information on exchange rate movements and currency exchange rate volatility of ASEAN-5 countries. This study employs data on the number of infection cases to measure COVID-19 information. The research period begins with the first case that occurred in each ASEAN-5 country until December 31st, 2020, using the GARCH research method. The results indicate that the COVID-19 outbreak information had a significant effect on exchange rate volatility but had no effect on the movement of the ASEAN-5 exchange rate in one day. Meanwhile, in five days, the COVID-19 information did not significantly affect the movement and volatility of the exchange rates of ASEAN-5 countries. The influence of COVID-19 outbreak information on the ASEAN-5 exchange rate, which is stronger in one day than five days supports the theory of exchange rate dynamics. This finding implies that COVID-19 information affects the exchange rate volatility of ASEAN-5 countries in the short term. For this reason, investors can be wiser in managing their investment portfolios, and regulators can implement policies to reduce volatility in the foreign exchange market.